Teaching Writing Procedure Text through Pictures to Grade IXB Students at MTs Negeri 4 Kota Palu - Marwiyah, Marwiyah; Said, Mawardin M.; Mukrim, Mukrim (Lembaga Yasin AlSys, 2025)
Many junior high school students struggle with writing skills, particularly in composing procedural texts, which require the ability to organize ideas, use appropriate vocabulary and grammar, and understand text structure. This study aims to investigate the effectiveness of using visual media in enhancing students’ ability to write procedural texts. The research was conducted at MTs Negeri 4 Kota Palu with Grade IXB students as subjects, employing a Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, implemented over two cycles. Data were collected through observation, interviews, field notes, and writing tests, and analyzed both qualitatively and quantitatively. The results show a significant improvement in students’ writing skills following the implementation of image-based instruction. In the first cycle, 57% of students met the Minimum Mastery Criterion (Kriteria Ketuntasan Minimal, KKM), which increased to 85% in the second cycle. Visual media proved effective in helping students comprehend content, logically sequence steps, and use imperative sentences more effectively. Additionally, the use of images enhanced student engagement, confidence, and learning motivation. The study concludes that integrating visual media, such as images, is an effective instructional strategy for developing procedural text writing skills. Practically, teachers are encouraged to incorporate visual media into writing instruction as an innovative approach that supports language development and classroom interaction.